Performance of Composite Membrane for Palm Oil Wastewater Treatment - Yuliwati, E.; Porawati, H.; Elfidiah, Elfidiah; Melani, A. (Journal of Applied Membrane Science & Technology, 2019)
Polyvinylidene fluoride (PVDF) composite membranes were prepared via phase inversion method by dispersing titanium dioxide (TiO2) in the dope solution. It is aimed to study the effects of TiO2 on the membrane surface properties and thus its separation performance. The PVDF membranes modified by various TiO2 contents were characterized with respect to cross-sectional structure, average pore size, effective porosity, hydrophilicity, permeability and rejection. Maximum values of membrane hydrophilicity, membrane porosity and average pore size were achieved upon addition of 1.95% TiO2. It is found that changes in the membrane surface properties are closely corresponded with the membrane fouling. The maximum flux and rejection of organic pollutants from palm oil wastewater were recorded at 82.5 L/m2 h and 98.8 %, respectively using PVDF composite membrane incorporated with 1.95% TiO2.